Millennial Generation Intentions in The Islamic Capital Market - Mira Rahmi; Dienni R Sholihah; Anita Nopiyanti (International Journal of Emerging Issues in Islamic Studies, 2023)
The millennial generation has great potential for capital market growth. However, the opportunity for the millennial generation to be able to invest in the Islamic capital market still needs to be investigated further. Therefore, to understand this issue, the unique characteristics of the millennial generation, such as understanding financial literacy, ease of access, and religiosity, are used as research variables in this study. As well as additional variables, namely lifestyle as a moderating variable and Islamic branding as an intervening variable related to the halal industry which will be used as a determining factor for millennial generation intentions in the Islamic Capital Market. The research method uses a descriptive method with a quantitative approach. The sampling technique used stratified random sampling, with the sample criteria being the millennial generation aged between 17-35 years, earning or having monthly money, and domiciled in the Jakarta area. The analysis technique uses multiple regression analysis to examine the relationship between research variables. By using primary data through questionnaires, 207 respondents were obtained. The results showed that the variables of financial literacy, ease of access, religiosity, and Islamic branding as intervening affected the millennial generation's investment intention, but lifestyle variables did not strengthen or weaken the financial literacy variable on investment intentions. The object of this research is limited to the millennial generation who live in Jakarta, so further research is needed for a broader millennial generation object.